The Difference in Breastfeeding Techniques of Primiparous Mothers Before and After Education on Correct Breastfeeding Techniques Using Audiovisual Media at Puskesmas Pakusari: The Difference in Breastfeeding Techniques of Primiparous Mothers Before and After Education on Correct Breastfeeding Techniques Using Audiovisual Media at Puskesmas Pakusari - Aswinda, Novemika Fitria; Sugijati (Fetus : Journal of Midwifery, 2025)
Many first-time mothers (primiparous women) experience difficulties in breastfeeding due to a lack of knowledge about proper breastfeeding techniques. This can lead to issues such as sore nipples, pain, and even breast engorgement, which may discourage some mothers from continuing to breastfeed. In fact, with appropriate education, these problems can be minimized. One method considered effective is the use of audiovisual media, as it is easier to understand and remember. This study aimed to determine the difference in breastfeeding techniques among primiparous mothers before and after receiving education on correct breastfeeding techniques through audiovisual media at Puskesmas Pakusari. The study employed a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of all breastfeeding primiparous mothers at Puskesmas Pakusari. Total sampling technique was applied, with a sample size of 30 respondents. Data were collected using the LATCH scoring system and analyzed statistically using the wilcoxon. The results showed that before the education, most respondents (90.0%) had breastfeeding techniques in the "fair" category, with only 10.0% in the "good" category. After the education, there was a significant improvement, with the majority of mothers (76.7%) categorized as "good" and only 23.3% remaining in the "fair" category. Based on the statistical test results, a p-value of 0.000 < 0.05 (p<α) was obtained, indicating that H1 was accepted, which means there was a significant difference in the breastfeeding techniques of primiparous mothers before and after receiving education on correct breastfeeding techniques through audiovisual media at Puskesmas Pakusari. It is recommended that primiparous mothers seek information about proper breastfeeding techniques, particularly through audiovisual media, to support the success of breastfeeding